Хозяин Гнилого болота: повесть / Л. И. Влодавец - Влодавец Леонид Игоревич (Страшилки, 2000)
7-8кл Экземпляры: (20181022) / Инвентарный номер: 30517 / Цена: 27.00 / Сис.шифр: Р2 / Авт.знак: В 58 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6